LOCAL VALENCY AND ITS SEMANTIC CORRESPONDENCE IN EVENTUALITY - Mukhayyo Ergashova, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In this article stressed about the concept of integrity and space of the Uzbek language, which consists of interrelated, interdependent elements.